Understanding the Role of Chemokines and Cytokines in Experimental Models of Herpes Simplex Keratitis. (9th April 2017) - Azher, Tayaba N.; Yin, Xiao-Tang; Stuart, Patrick M.
Abstract : Herpes simplex keratitis is a disease of the cornea caused by HSV-1. It is a leading cause of corneal blindness in the world. Underlying molecular mechanism is still unknown, but experimental models have helped give a better understanding of the underlying molecular pathology. Cytokines and chemokines are small proteins released by cells that play an important proinflammatory or anti-inflammatory role in modulating the disease process. Cytokines such as IL-17, IL-6, IL-1 α, and IFN- γ and chemokines such as MIP-2, MCP-1, MIP-1 α, and MIP-1 β have proinflammatory role in the destruction caused by HSV including neutrophil infiltration and corneal inflammation, and other chemokines and cytokines such as IL-10 and CCL3 can have a protective role. Most of the damage results from neutrophil infiltration and neovascularization. While many more studies are needed to better understand the role of these molecules in both experimental models and human corneas, current studies indicate that these molecules hold potential to be targets of future therapy.